Preparation method of glass optical fiber with low loss, high numerical aperture and high core-to-package ratio

By adjusting the proportion of oxide components and utilizing the properties of borosilicate glass to optimize the composition of the core and cladding glass, the problem of quartz fiber's inability to withstand high temperatures due to organic outer cladding in high-power lasers has been solved, achieving low loss and high Preparation of numerical aperture high core-to-cladding ratio glass optical fiber.

CN119330580APending Publication Date: 2025-01-21HFB PHOTONICS CO LTD

Patent Information

Application Number
CN202411450966.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In high-power lasers, the existing quartz fibers are not resistant to high temperatures, resulting in poor heat dissipation effect, which limits the development of high-power fibers.

Method used

By adjusting the relative proportions of alkali metal oxides, alkaline earth metal oxides and intermediate oxides, and utilizing the characteristics of borosilicate glass, the composition of the core and cladding glass is optimized to increase the numerical aperture and reduce the thermal expansion coefficient difference. , to achieve the preparation of glass optical fiber with high core-to-cladding ratio.

Benefits of technology

A low-loss, high-numerical-aperture, high-core-to-cladding ratio glass fiber was successfully prepared, with an NA of more than 0.46 and a core-to-cladding diameter ratio of more than 0.91, which solved the high-power all-glass optical fiber's high-temperature resistance and heat dissipation problems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005089114300000081
    Figure BDA0005089114300000081
  • Figure BDA0005089114300000111
    Figure BDA0005089114300000111
Patent Text Reader

Abstract

The invention relates to a preparation method of a glass optical fiber with low loss, high numerical aperture and high core-to-package ratio, which comprises the following steps: during composition design of a borosilicate fiber core and cladding glass, firstly, keeping the content ratio of alkali metal oxide, alkaline earth metal oxide and intermediate oxide basically constant; then, adjusting the relative content proportion of different oxides in the same kind of oxides, and meanwhile, utilizing the characteristic that the refractive index and the thermal expansion coefficient of borosilicate glass show that the refractive index change is obvious and the thermal expansion coefficient change is small along with the change of the content of boron oxide; the relative ratio of the content of silicon dioxide to the content of boron oxide is adjusted, and the numerical aperture and the thermal expansion coefficient difference value between the fiber core and the cladding glass are regulated in a bidirectional mode. Through subsequent fiber forming operation, preparation of the low-loss high-numerical-aperture high-core-to-package-ratio glass optical fiber with the numerical aperture reaching 0.46 or above and the core-to-package-ratio reaching 0.91 or above is achieved, and possibility is provided for preparation and application of the low-loss thin-cladding all-glass optical fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of optical glass materials, and in particular to a method for preparing a low-loss, high-numerical-aperture, high-core-to-cladding ratio glass optical fiber. Background Art

[0002] Quartz fiber is currently the first choice of fiber material in high-performance fiber lasers. The numerical aperture (NA) between the core and the inner cladding is generally below 0.12, and the NA between the inner cladding and the outer cladding generally needs to reach about 0.46. Currently, commercial quartz fiber uses organic matter as its outer cladding material. With the further increase of laser output power, the defect of organic matter that is not resistant to high temperature becomes more and more prominent, which greatly hinders the overall heat dissipation effect of the optical fiber and inhibits the development of high-power quartz fiber. Compared with organic matter, the high temperature resistance of glass is significantly higher. Therefore, the demand for high-power all-glass optical fiber is becoming more and more urgent.

[0003] We have made some explorations in the research and development of high-power all-glass optical fibers, among which the preparation technologies of the announcement number CN103951267B, named silicate all-glass optical fiber for high-power fiber lasers, and the announcement number CN103964696B, named phosphate silicate all-glass hybrid optical fiber for high-power fiber lasers, have been authorized for invention patents. In these patents, without compromising the environmental stability of the glass optical fiber, the silicate glass composition is optimized and adjusted, and the NA between the inner and outer claddings can reach about 0.46, which can effectively replace organic matter as the outer cladding of the optical fiber. Therefore, the research on silicates and other multi-component glasses is expected to provide good material support for the generation of high-performance fiber lasers.

[0004] During the development of silicate glass optical fiber, it was found that when the content ratio of each component such as alkali metal oxide, alkaline earth metal oxide and intermediate oxide is basically constant, and the total amount of the same type of oxide remains unchanged, by adjusting the relative content ratio of each specific oxide in the same type of oxide, the NA can only be less than 0.25. On the other hand, when the ratio of the inner and outer cladding diameters of the optical fiber is less than 0.85, and the difference in the thermal expansion coefficient of the inner and outer cladding glass is greater than 10×10 -7 / ℃, although the optical fiber can be successfully drawn, there is a certain probability of failure. However, when the ratio of the inner and outer cladding diameters of the optical fiber is greater than 0.85, or continues to increase to close to 0.91, the optical fiber made of the two glasses with the above-mentioned difference in thermal expansion coefficient is difficult to be successfully drawn. Summary of the invention

[0005] The purpose of the present application is to provide a method for preparing a low-loss, high-numerical-aperture, high-core-to-clad ratio glass optical fiber, aiming to solve the problems existing in the prior art.

[0006] The embodiment of the present application provides a method for preparing a low-loss, high-numerical-aperture, high-core-to-cladding ratio glass optical fiber. When designing the composition of the core and cladding glass, the content ratio of the components of alkali metal oxides, alkaline-earth metal oxides, and intermediate oxides that can change the physical and chemical properties of the glass is kept basically constant; when the total amount of the same type of oxides remains unchanged, the relative ratio between different oxides of the same type of oxide is adjusted, and at the same time, the relative ratio between the contents of silicon dioxide (SiO2) and boron oxide (B2O3), the main unit components of the glass structure, is further adjusted by utilizing the characteristics that the refractive index and thermal expansion coefficient of borosilicate glass change significantly with the boron oxide content, while the thermal expansion coefficient changes slightly, so as to increase the NA between the core and cladding glass and reduce the difference in thermal expansion coefficient between the core and cladding glass; after determining the composition of the core and cladding glass, the preparation of a low-loss, high-numerical-aperture, high-core-to-cladding diameter ratio glass optical fiber is achieved through high-temperature melting, preform rod preparation, and precise control of the tension value of the traction wheel in the fiber-forming process.

[0007] Furthermore, the diameter ratio of the core to the cladding is greater than 0.85.

[0008] Further, the alkali metal oxide includes one or more of lithium oxide (Li2O), sodium oxide (Na2O) and potassium oxide (K2O), the alkaline earth metal oxide includes one or more of magnesium oxide (MgO), calcium oxide (CaO) and barium oxide (BaO), and the intermediate oxide includes one or more of aluminum oxide and zinc oxide.

[0009] Furthermore, the difference between the sum of the molecular percentages of alkali metal oxides in the core glass composition and the sum of the molecular percentages of alkali metal oxides in the cladding glass composition is not greater than 4%, the difference between the sum of the molecular percentages of alkaline earth metal oxides in the core glass composition and the sum of the molecular percentages of alkaline earth metal oxides in the cladding glass composition is not greater than 4%, and the difference between the sum of the molecular percentages of intermediate oxides in the core glass composition and the sum of the molecular percentages of intermediate oxides in the cladding glass composition is not greater than 6%.

[0010] Furthermore, the molecular percentage of B2O3 in the core and cladding glass is less than or equal to 15%.

[0011] Furthermore, the difference in thermal expansion coefficient between the core and cladding glass is less than 5×10 -7 / ℃.

[0012] Furthermore, the tension value of the traction wheel during the fiber forming process is less than 10 grams.

[0013] Furthermore, the method specifically includes the following steps:

[0014] S1. Design the core and cladding glass compositions separately: design the composition contents of the main structural unit components SiO2, alkali metal oxides, alkaline earth metal oxides, intermediate oxides and B2O3 of the glass in turn; the difference between the sum of the molecular percentages of alkali metal oxides in the core glass composition and the sum of the molecular percentages of alkali metal oxides in the cladding glass composition is not more than 4%, the difference between the sum of the molecular percentages of alkaline earth metal oxides in the core glass composition and the sum of the molecular percentages of alkaline earth metal oxides in the cladding glass composition is not more than 4%, the difference between the sum of the molecular percentages of intermediate oxides in the core glass composition and the sum of the molecular percentages of intermediate oxides in the cladding glass composition is not more than 6%, the molecular percentage contents of B2O3 in the core and cladding glasses are both less than or equal to 15%, and the rest are SiO2; further adjust the relative proportions of the contents of the specific oxides in the same type of oxides, as well as the relative proportions of the contents of SiO2 and B2O3, so as to satisfy the difference in the thermal expansion coefficients of the core and cladding glasses being less than 5×10 -7 / ℃ and the condition of numerical aperture greater than 0.25;

[0015] S2, glass preparation: weigh various glass raw materials designed in S1 in order according to the amount of glass to be prepared; place the uniformly mixed glass raw materials in a high-temperature furnace preheated to 1500-1600°C for a period of time to melt into glass liquid; pour the glass liquid into a preheated cast iron mold, put it into an annealing furnace after it is fully solidified, cool it to room temperature, and then take it out to obtain a large piece of glass for the core or cladding;

[0016] S3. Fiber preparation: The obtained large piece of glass is processed into a preform rod, and then the preform rod is placed in a fiber drawing furnace for fiber drawing operation, ultimately achieving the successful preparation of low-loss, high numerical aperture, and high core-cladding diameter ratio glass optical fiber.

[0017] Beneficial technical effects of the present invention:

[0018] When designing the composition of the core and cladding glass, the present invention first maintains the content ratio of each component such as alkali metal oxides, alkaline earth metal oxides and intermediate oxides to be basically constant, so that the physical and chemical properties of the two glasses can be kept basically the same, and the additional optical fiber transmission loss caused by the large difference in physical and chemical properties can be reduced. Based on the fact that the NA obtained by adjusting the relative proportion of the content of each specific oxide in the same type of oxide can only be less than 0.25, the refractive index and thermal expansion coefficient of borosilicate glass show different change trends with the change of B2O3 content, that is, the refractive index changes significantly while the thermal expansion coefficient changes slightly. By optimizing and controlling the content of SiO2 and B2O3, the main structural unit components of the glass, the purpose of increasing the NA between the core and the cladding and reducing the difference in their thermal expansion coefficients is achieved at the same time, making it possible to prepare a glass optical fiber with a high core-to-cladding ratio. Through the method of the present invention, the difference in the thermal expansion coefficients of the inner and outer cladding glasses is controlled to be less than 5×10 -7 / ℃, after optimizing the high-temperature melting of glass, the preparation of preform rods and the precise control of the tension value of the traction wheel in the subsequent fiber-forming process, the successful preparation of low-loss, high-numerical aperture, high-core-cladding ratio glass optical fiber with NA above 0.46 and core-cladding diameter ratio above 0.91 can be achieved. Finally, the preparation of low-loss all-glass optical fiber with high numerical aperture and high core-cladding ratio that is difficult to achieve with quartz all-glass optical fiber is realized, which provides possibilities for the preparation and application of low-loss thin-cladding glass optical fiber.

[0019] The present invention creatively proposes a method for preparing a low-loss, high-numerical-aperture, high-core-cladding-ratio glass optical fiber based on glass composition design. The method is simple and reasonable, and not only maintains the stability of the overall properties of the core and cladding glass, which is beneficial to reducing the transmission loss of the optical fiber, but also utilizes the special effect of B2O3 on the physical and chemical properties of silicate glass, and realizes the preparation of a high-numerical-aperture, high-core-cladding-ratio all-glass optical fiber, which provides the possibility for the preparation and application of low-loss, thin-cladding glass optical fiber. DETAILED DESCRIPTION

[0020] The technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] A method for preparing a low-loss, high-numerical-aperture, high-core-to-clad ratio glass optical fiber comprises the following steps:

[0022] S1. Design the core and cladding glass composition separately:

[0023] The composition contents of the main structural unit components SiO2, alkali metal oxides, alkaline earth metal oxides and intermediate oxides as well as B2O3 of the glass are designed in sequence: the total content of the same type of oxides (alkali metal oxides, alkaline earth metal oxides and intermediate oxides) in the core and cladding compositions is kept not much changed: that is, the difference between the total molecular percentage of alkali metal oxides in the core glass composition and the total molecular percentage of alkali metal oxides in the cladding glass composition is not more than 4%, the difference between the total molecular percentage of alkaline earth metal oxides in the core glass composition and the total molecular percentage of alkaline earth metal oxides in the cladding glass composition is not more than 4%, and the difference between the total molecular percentage of intermediate oxides in the core glass composition and the total molecular percentage of intermediate oxides in the cladding glass composition is not more than 6%.

[0024] Under the condition that the total amount of the same type of oxides remains unchanged, by adjusting the relative proportion of the content of each specific oxide in the same type of oxide, as well as the relative proportion of the content between SiO2 and B2O3, the refractive index and thermal expansion coefficient of the glass are optimized and regulated, so that the numerical aperture between the core and cladding glass is greater than 0.25, and the difference in thermal expansion coefficient is less than 5×10 -7 / ℃. The specific oxides among the alkali metal oxides are one or more of Li2O, Na2O and K2O, and the composition and proportion are arbitrarily adjusted according to the set glass parameters. The specific oxides among the alkaline earth metal oxides are one or more of MgO, CaO and BaO, and the composition and proportion are arbitrarily adjusted according to the set glass parameters. The specific oxides among the intermediate oxides are one or more of aluminum oxide and zinc oxide, and the composition and proportion are arbitrarily adjusted according to the set glass parameters. The molecular percentage content of B2O3 in the core and cladding glasses is less than or equal to 15%. In a preferred embodiment, the molecular percentage content of B2O3 in the core glass is 6 times the molecular percentage content of B2O3 in the cladding glass, and the rest is SiO2, so that the sum of all components is 100%.

[0025] S2. Glass preparation:

[0026] S2.1. Weigh various glass raw materials designed in S1 in order according to the amount of glass to be prepared, and mix them evenly;

[0027] S2.2, placing the uniformly mixed glass raw materials in a high-temperature furnace preheated to 1500-1600°C for a period of time to melt into glass liquid;

[0028] S2.3, pouring the glass liquid into a preheated cast iron mold, putting it into an annealing furnace after it is fully solidified, cooling it to room temperature, and then taking it out to obtain a large piece of glass for the core or cladding;

[0029] S3. Fiber preparation: The obtained large piece of glass is processed into a preform rod, and then the preform rod is placed in a fiber drawing furnace for fiber drawing operation. The tension value of the traction wheel during the fiber drawing process is preferably less than 10 grams, and finally the successful preparation of low-loss, high-numerical aperture, and high core-to-shell ratio glass optical fiber is achieved.

[0030] After the above steps, borosilicate glass optical fiber can be successfully drawn, and its NA is greater than 0.25, and the difference in thermal expansion coefficient between the core and cladding glass is less than 5×10 -7 / ℃, the core-cladding diameter ratio is greater than 0.85, and it has the characteristics of low loss, high numerical aperture and high core-cladding ratio.

[0031] The following is explained in detail with reference to the specific embodiments:

[0032] The five embodiments shown in Table 1 are the sum of the molecular percentages of the various oxide contents in the various designed core and cladding combinations, R2O represents alkali metal oxides, RO represents alkaline earth metal oxides, R2O3 represents intermediate oxides, Δα represents the difference in thermal expansion coefficients (×10 -7 / ℃), NA represents the numerical aperture, β represents the core-cladding diameter ratio, and T represents the traction wheel tension value (g).

[0033] Table 1 Glass composition (molecular percentage) and properties of each example

[0034]

[0035] Embodiment 1:

[0036] S1-1. In the glass composition design of this embodiment, the core and cladding components do not contain B2O3, and the R2O content is quite different. The obtained Δα is about 15.4×10 -7 / °C, NA is 0.29.

[0037] S1-2. Accurately weigh the various oxides corresponding to Example 1 according to the actual raw material addition amount required to prepare 400 grams of glass, then carefully and evenly mix them well in an agate mortar and put them into a platinum crucible. Then put them together with the crucible into a high-temperature furnace that has been pre-heated to 1500-1600°C and is equipped with a high-purity atmosphere protection device, heat and melt them into glass liquid, and keep them at this temperature for 24 hours to allow various raw materials to fully react. Then, pour the glass liquid into a preheated cast iron mold, put it into an annealing furnace after it is fully solidified, cool it to room temperature, and then take it out to obtain a large piece of colorless glass.

[0038] S1-3. Process the colorless bulk glass obtained in step S1-2 into a preform rod so that β is about 0.82.

[0039] S1-4. The processed preform rod is placed in a drawing furnace with high-purity atmosphere protection for fiber drawing. Although the T variation range is maintained at about 7-9g during the drawing process, the optical fiber is still broken and the preparation of glass optical fiber is not achieved.

[0040] Embodiment 2:

[0041] S2-1. The glass composition design in this embodiment is quite different. B2O3 is added to the core glass composition, while the cladding is the same as in Embodiment 1 and does not contain B2O3. The R2O content in the core and cladding components is the same, but the RO and R2O3 contents are quite different, and their Δα is reduced to 10.9×10 -7 / ℃, NA can reach 0.47.

[0042] S2-2, the glass preparation steps are exactly the same as S1-2.

[0043] S2-3. Process the colorless bulk glass obtained in step S2-2 into a preform rod so that β is about 0.84.

[0044] S2-4. The processed preform rod is placed in a drawing furnace with high-purity atmosphere protection for fiber drawing operation. During the drawing process, the T variation range is controlled to be approximately 14-16g, and the preparation of glass optical fiber is successfully achieved.

[0045] Embodiment 3:

[0046] S3-1. The composition design of the glass in this embodiment is exactly the same as that in embodiment 2, so their Δα and NA are also exactly the same. The only difference is that β is increased to 0.87.

[0047] S3-2, the glass preparation steps are exactly the same as S1-2.

[0048] S3-3. Process the colorless bulk glass obtained in step S3-2 into a preform rod so that β is about 0.87.

[0049] S3-4. The processed preform rod is placed in a drawing furnace with high-purity atmosphere protection for fiber drawing. Although the T variation range is reduced to about 8-10g during the drawing process, the optical fiber is still broken and the preparation of glass optical fiber is not achieved.

[0050] Embodiment 4:

[0051] S4-1. In the glass composition design of this embodiment, the core glass is exactly the same as that of the embodiment 2. The cladding glass and the core glass are designed in the same way and the composition is also within the variation range of the contents of R2O, RO and R2O3 in the technical solution of the present invention. B2O3 is added and the content of B2O3 is greatly different from that of the core glass, which reduces their Δα to 2.0×10-7 / ℃, NA is about 0.37.

[0052] S4-2, the glass preparation steps are exactly the same as S1-2.

[0053] S4-3. Process the colorless bulk glass obtained in step S4-2 into a preform rod so that β is further increased to about 0.91.

[0054] S4-4. The processed preform rod is placed in a drawing furnace with high-purity atmosphere protection for fiber drawing operation. During the drawing process, the T variation range is controlled to be approximately 7-9g, and the preparation of glass optical fiber is successfully realized.

[0055] Embodiment 5:

[0056] S5-1. In the glass composition design of this embodiment, in order to continue to increase NA, the core glass maintains the glass composition design criteria in Example 4. While the total amount of alkali metal oxides and the total amount of alkaline earth metal oxides are kept constant at 20.0% and 17.6%, respectively, the relative proportions of the specific alkali metal oxides and alkaline earth metal oxides are adjusted as shown in Table 2, thereby achieving a core glass composition design with a higher refractive index.

[0057] Table 2 Specific oxide composition of the core glass in Example 4 and Example 5 (molecular percentage)

[0058]

[0059] The cladding glass composition is still the same as that in Example 4. This adjustment makes their Δα slightly increase to 4.6×10 -7 / ℃, NA is about 0.46.

[0060] S5-2, the glass preparation steps are exactly the same as S1-2.

[0061] S5-3. Process the colorless bulk glass obtained in step S5-2 into a preform rod so that β is 0.91, the same as in Example 4.

[0062] S5-4. The processed preform rod is placed in a drawing furnace with high-purity atmosphere protection for fiber drawing operation. During the drawing process, the T variation range is controlled to be about 6-8g, and the preparation of glass optical fiber is successfully achieved.

[0063] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered as exemplary and non-restrictive in all respects.

Claims

1. A method for preparing a low-loss, high-numerical-aperture, high-core-to-clad-ratio glass optical fiber, characterized in that: When designing the composition of borosilicate core and cladding glass, the content ratio of alkali metal oxides, alkaline earth metal oxides and intermediate oxides that can change the physical and chemical properties of the glass is kept basically constant; when the total amount of oxides of the same type remains unchanged, the relative ratio of the content of each specific oxide in the same type of oxide is adjusted, and at the same time, the relative ratio of the content of silicon dioxide and boron oxide, the main unit components of the glass structure, is further adjusted by utilizing the characteristics that the refractive index and thermal expansion coefficient of borosilicate glass change significantly with the change of boron oxide content, while the thermal expansion coefficient changes slightly, so as to increase the numerical aperture between the core and cladding glass and reduce the difference in thermal expansion coefficient between the core and cladding glass; after determining the composition of the core and cladding glass, the preparation of borosilicate glass optical fiber with low loss, high numerical aperture and high core-to-cladding diameter ratio is realized through high-temperature melting, preform rod preparation and precise control of the tension value of the traction wheel in the fiber-forming process.

2. The method for preparing a low-loss, high-numerical-aperture, high-core-to-clad-ratio glass optical fiber according to claim 1, characterized in that: The diameter ratio of the core to the cladding is greater than 0.

85.

3. The method for preparing a low-loss, high-numerical-aperture, high-core-to-clad-ratio glass optical fiber according to claim 1, characterized in that: The alkali metal oxide includes one or more of lithium oxide, sodium oxide and potassium oxide, the alkaline earth metal oxide includes one or more of magnesium oxide, calcium oxide and barium oxide, and the intermediate oxide includes one or more of aluminum oxide and zinc oxide.

4. The method for preparing a low-loss, high-numerical-aperture, high-core-to-clad-ratio glass optical fiber according to claim 1, characterized in that: The difference between the sum of the molecular percentages of alkali metal oxides in the core glass composition and the sum of the molecular percentages of alkali metal oxides in the cladding glass composition is not greater than 4%, the difference between the sum of the molecular percentages of alkaline earth metal oxides in the core glass composition and the sum of the molecular percentages of alkaline earth metal oxides in the cladding glass composition is not greater than 4%, and the difference between the sum of the molecular percentages of intermediate oxides in the core glass composition and the sum of the molecular percentages of intermediate oxides in the cladding glass composition is not greater than 6%.

5. The method for preparing a low-loss, high-numerical-aperture, high-core-to-cladding ratio glass optical fiber according to claim 1, characterized in that: The molecular percentage of boron oxide in the core and cladding glass compositions is less than or equal to 15%.

6. The method for preparing a low-loss, high-numerical-aperture, high-core-to-clad-ratio glass optical fiber according to claim 1, characterized in that: The difference in thermal expansion coefficient between the core and cladding glass is less than 5×10 -7 / ℃.

7. The method for preparing a low-loss, high-numerical-aperture, high-core-to-clad-ratio glass optical fiber according to claim 1, characterized in that: The tension value of the traction wheel during the fiber forming process is less than 10 grams.

8. The method for preparing a low-loss, high-numerical-aperture, high-core-to-clad-ratio glass optical fiber according to claim 1, characterized in that: The specific steps include: S1. Design the core and cladding glass compositions respectively: design the composition contents of the main structural unit components of glass, silicon dioxide, alkali metal oxides, alkaline earth metal oxides, intermediate oxides and boron oxide in sequence; The difference between the sum of the molecular percentages of alkali metal oxides in the core glass composition and the sum of the molecular percentages of alkali metal oxides in the cladding glass composition is not greater than 4%, the difference between the sum of the molecular percentages of alkaline earth metal oxides in the core glass composition and the sum of the molecular percentages of alkaline earth metal oxides in the cladding glass composition is not greater than 4%, the difference between the sum of the molecular percentages of intermediate oxides in the core glass composition and the sum of the molecular percentages of intermediate oxides in the cladding glass composition is not greater than 6%, the molecular percentage content of boron oxide in the core and cladding glass compositions is less than or equal to 15%, and the rest is silicon dioxide; the relative proportions of the contents of the specific oxides in the same type of oxides, as well as the relative proportions of the contents of silicon dioxide and boron oxide are further adjusted to meet the requirement that the difference in thermal expansion coefficients of the core and cladding glass is less than 5×10 -7 / ℃ and the condition of numerical aperture greater than 0.25; S2, glass preparation: weigh various glass raw materials designed in S1 in order according to the amount of glass to be prepared; place the uniformly mixed glass raw materials in a high-temperature furnace preheated to 1500-1600°C for a period of time to melt into glass liquid; pour the glass liquid into a preheated cast iron mold, put it into an annealing furnace after it is fully solidified, cool it to room temperature, and then take it out to obtain a large piece of glass for the core or cladding; S3. Fiber preparation: The obtained large piece of glass is processed into a preform rod, and then the preform rod is placed in a fiber drawing furnace for fiber drawing operation, and finally the successful preparation of borosilicate glass optical fiber with low loss, high numerical aperture and high core-to-clad ratio is achieved.

Citation Information

Patent Citations

  • Silicate all-glass optical fiber for high-power fiber lasers

    CN103951267B

  • Phosphate-silicate all-glass hybrid fibers for high-power fiber lasers

    CN103964696B

Cited By

  • Illumination optical fiber and preparation method and application thereof

    CN120965115A